Bail : right or discretion / Ainon A. Rahman - A. Rahman, Ainon (Faculty of Law, 1987)
In Malaysia, there are indeed an excessive number of remand prisoners who are swelling the country's prison as well as police lock-ups as opposed to being released on bail while awaiting trial. These pre-trial detainees were remanded despite the fact that the law presumed them to be innocent until proven quilty. The high rate of pre-trial detention certainly seemed to warrant an investigation to determine both the causes and consequences of pre-trial detention. Thus, it significant that due to the unsatisfactory conditions of pre-trial detention,has urged the courts to increase the use of bail as much as possible or at least reduce the period of custody before trial. The granting or denial of bail in Malaysia has in effect remained a dicretionary function of the judiciary. This discretion vested to the authorities concerned must be exercised judicially and not arbitrary although the granting or rejecting of bail is the prerogative of the courts. If the courts become too strict, perhaps thousands of innocent people will find themselves detained in custody for an excessive period. That would make useless of the presumption of innocence. On the other hand, if the Magistrates and Judges are too lenient, there is a grave danger that serious whereby public interest will be interfered with the continuance of criminal acts done by the people who have been released on bail.